تفسیر اختریہ کی روشنی میں اہل کتاب سے نکاح کے مسئلہ کا تحقیقی جائزہ : Research Review Of The Issue Of Nikah From Ahl E Kitab In The Light Of Tafsir Akhtiriya - Asif, Muhammad; Abdul Tahir (Journal of Quranic and Social Studies, 2022)
In this article we are presenting a research on intra religion marriages in lights of Tafseer AKHTARYA.The Outer of Tafseer mentioned above Molana AKHTAR MUHAMMAD S/o DILASA KHAN was born on 09th of October 1916 in Shair shah nearby kandhar AFGHANISTAN. He belongs to Mengele tribes of Bloch tribes. He had good command on various languages like Brahui, Balochi, Urdu, Pashto, Arabic and Persian.He choose a local language Brahui for hi famous Tafseer named Tafseer AKHTARYA. This is a very helpful for local Brahui people. He completed his TAFSEER in 6 volumes.Intra religion marriages very common now a days. It is permissible for a Muslim men to marry an Ahl-e-kitab girl. The quantic term all-e-kitbag means those who believe on a religion heavenly religion but it is not a good practice. Islamic scolders dislike this practice unanimously.